Milk fatty acid profile in different genetic groups and age of buffaloes - Mettamehtar, K.; Tuntivisoottikul, K.; Takeungwongtrakul, S. (International Journal of Agricultural Technology, 2021)
Thirty-seven fatty acids were identified in 40 buffalo milk samples. Nineteen of the totals identified fatty acids were found in all samples. Sixteen fatty acids were detected in some samples. ɤ-Linolenic acid (C18:3n6) and cis-11,14,17-eicosatrienoic acid (C20:3n3) were not found in buffalo milk. Milk from 50% Murrah crossbreds had the highest content of C6:0, C8:0, C10:0, C12:0, C14:0, C16:0, and C18:1n9t (p£0.05). There were no significant differences in the averages of docosahexaenoic acid (C22:6n3) contents between 100% Murrah and 50% Murrah crossbreds. Averages of SFA and total fatty acids in 50% Murrah crossbreds were higher than those of the 100% Murrah. The factor of age within different genetic groups affected six fatty acids such as C6:0, C8:0, C10:0, C12:0, C16:0, and C22:6n3 (p£0.05). The traits in 50% Murrah crossbreds which were younger than 7 years old and older than 9 years old were higher than those in others, except for C6:0 and C22:6n3, in which the 50% Murrah, that were older than 9 years old were the highest. With regards to the Murrah purebreds, no significant differences in the traits of the different studied ages were noticed. The factor also affected the SFA and total fatty acids contents (p£0.05) but did not influence MUFA and PUFA (p>0.05).